Effect of forced-molting methods and rearing temperatures on the performance and organ biometrics of laying hens - Sgavioli, S. [UNESP] (2013)
An experiment was conducted to evaluate the biometrics of organs (ovary, oviduct, liver, proventriculus and gizzard) of laying hens submitted to different forced-molting methods of molt and maintained at three different temperature. Organs were evaluated after molting and resting period. Six hundred birds were distributed according to a completely randomized experimental design in a 5x3 factorial arrangement (forced-molting methods x environmental temperatures) into 15 treatments with 5 replicates of 8 birds each. The molting methods applied were the dietary inclusion of 90%, 70%, 50% of alfalfa, 2,800 ppm zinc oxide, or total feed restriction. Birds were kept at ±20 oC, ±27 oC, or ±35 oC. Data were submitted to analysis of variance and means were compared by orthogonal and polynomial contrasts. The traditional forced-molting method (feed fasting) resulted in adequate performance. However, as the aim of the present study was to find an alternative method to feed fasting, the highest dietary alfafa inclusion level (90%) was shown to be efficient compared with other methods, particularly when hens were kept at high temperature. Therefore, this alternative forced-molting may be applied, especially when bird welfare is taken into consideration.